The Effect of Work Environment on Employee Loyalty Mediated by Employee Satisfaction at XYZ Company - Aldhia Rachmi, Riezfa; Siti Hadijah, Hady; Setiawan, Yana (Journal of Accounting and Finance Management, 2024)
Employees are an asset to the company. The success of a company is highly dependent on the quality of its employees. Changes in the era of globalization demand the existence of employees who have the ability to compete. As one of the private companies, of course, company XYZ must be able to have qualified employees in order to excel from similar competitors. One of the aspects possessed by qualified employees is a high level of loyalty. This study aims to evaluate the level of loyalty of employees of XYZ company that is affected by the work environment and mediated by employee satisfaction. This study uses a verifiable descriptive approach, with a sample of 68 informants. Data collection was carried out through a questionnaire with data processing using SEM-PLS. The findings of the study show that the work environment has a significant effect on employee loyalty levels. On the continuum line, the work environment and employee loyalty are in the high category. This research also highlights the need for XYZ company to improve the professional equipment used to support Employee Loyalty which ultimately affects the company's performance. This research also highlights the need for XYZ company to improve the professional equipment used to support employee loyalty which ultimately affects the company's performance.